Energetic economic and environmental analysis of an integrated waste to energy- cryogenic air separation plant - Tafone, Alessio (2017)
This work investigates the thermodynamic feasibility of the integration of a cryogenic Air Separation unit (ASU) with a Waste-to-Energy (WtE) power plant in order to enhance the combustion with an oxygen enriched air flow. The main benefit of using oxygen enrichment in an incineration system is represented by the reduction of the sensible heat as the quantity of nitrogen in the flue gas will be decreased. In addition, the possibility to exploit the secondary products of the cryogenic separation as part of Liquid Air Energy Storage (LAES) system has been considered. To further improve the thermal efficiency and net power output of the waste to energy system, different cycle configurations have been modelled; the thermodynamics and processes of the main units, as well as the waste combustion model, are described in details together with the main assumptions and constraints. The WtE-ASU integrated systems are compared in terms of different performance indices such as thermal efficiency and power output as well as the concentration of pollutant emissions. Moreover, since the benefits of using an oxygen enriched air flow must offset the added cost of oxygen production, the operative and capital cost have been analysed in order to determine whether or not the introduction of ASU is economically advantageous. The results show that, under opportune conditions, the penalty in energy efficiency coming from the integration between the Waste-to-Energy plant and the Air Separation Unit can be compensated, both economically and environmentally, by means of the by-products valorisation.